Decisive diagnostic clue for infectious abdominal aortic aneurysm caused by Arthrobacter russicus in a diabetic elderly woman with renal dysfunction: A case report and literature review - Yamamoto, Hiroyuki; Fukushima, Yasuto; Ikeda, Yoshihiko; Suda, Tomoyuki; Goto, Mieko; Isogai, Jun; Hashimoto, Toru; Takahashi, Takashi; Ogino, Hidemitsu (Frontiers in Cardiovascular Medicine, 2022)
Infectious aortic aneurysm (IAA) can be a rare but potentially fatal sequela of infectious inflammatory disease of the aortic wall with a high incidence of rupture. The definitive diagnosis is based on vascular imaging of the aneurysm using contrast-enhanced computed tomography and identification of the causative microorganism from positive blood cultures. However, IAA remains extremely difficult to diagnose and treat in patients with prior antimicrobial treatment or with renal dysfunction. Here we describe a case of an 85-year-old woman with IAA caused by Arthrobacter russicus presenting with abdominal pain and fever that was initially diagnosed as a presumptive urinary tract infection and treated with empiric antimicrobial therapy. However, persistent abdominal pain with increased serological inflammation necessitated further evaluation. Unenhanced multimodality imaging considering the renal dysfunction revealed infectious aortitis of the infrarenal abdominal aorta, together with the initial culture results, leading to the tentative diagnosis of Klebsiella pneumoniae aortitis. Thereafter, serial monitoring with unenhanced magnetic resonance angiography (MRA) using thin-slab maximum intensity projection revealed acute aortic expansion strongly suggestive of a pseudoaneurysm that was successfully treated with early surgical repair under adequate infection control. Despite negative Gram staining and tissue culture results for the excised aortic wall, a definitive diagnosis of IAA secondary to A. russicus rather than K. pneumoniae was finally made by confirming the histologic findings consistent with IAA and the identification of A. russicus 16S rRNA on the resected aortic wall. The patient also developed a vascular graft infection during the postoperative course that required long-term systemic antimicrobial therapy. This case highlights the value of unenhanced MRA in the early detection of IAA in patients with renal dysfunction and the importance of a molecular diagnosis for identifying the causative microorganism in cases of culture- or tissue-negative IAA.